MAKNA KEJAHATAN STRUKTURAL KORUPSI DALAM PERSPEKTIF TEORI STRUKTURASI ANTHONY GIDDENS - Thoyibbah, Imadah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2015)
Corruption is the reality of crime that can not be separated from the structure and human agency. The perspective of structuration theory emphasizes the duality relation between agents and structures. The structure includes the rules and resources and the social systems are mobilized in space-time by the social agents. Corruption as a structural crime involving micro structures and macro structures. First, corruption is a crime that occurs due to banality (omission/habituation) whose motive is greed, dishonesty, arrogance, pettiness, shallowness of thought and the subjective satisfaction. Motifs are encased in a system of production and reproduction of social activity that is dialectic. Secondly, corruption is sustained by the conditions of a globalized modernity as a result of events like the separation of time and spice, the development of disembedding mechanism of localized context, and the reflexive appropriation of knowledge. Agents are those that have a value of intervention (effect) against a corrupt act. Various efforts to justify acts of corruption is a form of rationalization of actions by human agents as creative and reflexive beings. Their motive is to avoid moral responsibility and social law. Social change can be done by 'deroutinization' of structure or distancing by reflexive monitoring of structure while constraining and enabling the seeds of corruption that involves the structure of signification, domination, and legitimation in the constitutions of society.